2017
DOI: 10.5194/bg-14-2641-2017
|View full text |Cite
|
Sign up to set email alerts
|

20th century changes in carbon isotopes and water-use efficiency: tree-ring-based evaluation of the CLM4.5 and LPX-Bern models

Abstract: Abstract. Measurements of the stable carbon isotope ratio (δ 13 C) on annual tree rings offer new opportunities to evaluate mechanisms of variations in photosynthesis and stomatal conductance under changing CO 2 and climate conditions, especially in conjunction with process-based biogeochemical model simulations. The isotopic discrimination is indicative of the ratio between the CO 2 partial pressure in the intercellular cavities and the atmosphere (c i /c a ) and of the ratio of assimilation to stomatal condu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(71 citation statements)
references
References 159 publications
(210 reference statements)
5
66
0
Order By: Relevance
“…Two exceptions to the relatively weak increase in iWUE were the low and mid elevation sites of the west transect, where increases were nearly double those of other sites (Figures c and a). The increases at these sites were far more in line with observations of temporal changes in iWUE globally (Keller et al., ; Peñuelas et al., ; Silva & Anand, ).…”
Section: Discussionsupporting
confidence: 84%
“…Two exceptions to the relatively weak increase in iWUE were the low and mid elevation sites of the west transect, where increases were nearly double those of other sites (Figures c and a). The increases at these sites were far more in line with observations of temporal changes in iWUE globally (Keller et al., ; Peñuelas et al., ; Silva & Anand, ).…”
Section: Discussionsupporting
confidence: 84%
“…With one exception (Battipaglia et al, ), free‐air carbon dioxide enrichment (FACE) experiments studying the effects of elevated c a on plants and ecosystems under natural, open‐air conditions have shown responses broadly consistent with the third strategy, that is constant c i / c a (Ainsworth & Long, ; Gimeno et al, ; De Kauwe et al, ), giving rise to the expectation that plants growing in normal conditions should behave accordingly. Most tree‐ring studies in natural environments have yielded results consistent with this strategy (Frank et al, ; Keller et al, ; Peñuelas et al, ; Saurer et al, ). However, there is also empirical support for plants following scenario (i) with constant c i (Dorado Liñán et al, ) or scenario (ii) where c i increases at the same rate as c a (McCarroll et al, ; Treydte et al, ).…”
Section: Trends Reported In the Literature From Observationsmentioning
confidence: 94%
“…Leaf-level studies using stable carbon isotopes in tree rings, employing Equation (4), have indicated an increase of iWUE leaf of 0.2 ± 0.1% year -1 over the 20th century (e.g. Frank et al, 2015;Keller et al, 2017;Peñuelas, Canadell, & Ogaya, 2011;Saurer et al, 2014;Silva & Anand, 2013), approximately proportional to the recent increase in c a (Figure 1b). Some of these studies have shown a weakening iWUE leaf response to c a towards the end of the 20th century in regions where increases both in temperature and in D may have offset the increase in iWUE leaf due to increasing c a (Gagen et al, 2011;Waterhouse et al, 2004).…”
Section: Trends Rep Orted In the Liter Ature From Obs Ervati On Smentioning
confidence: 99%
See 2 more Smart Citations